Influence of the color scale in qualitative assessment of myocardial perfusion imaging - Figueiredo, Andreia (2022)
Introduction – Myocardial perfusion imaging (MPI) is a widely accepted study applied in the diagnosis and follow-up of coronary artery disease. Interpretation of myocardial perfusion images requires visual analysis of the reconstructed slices. The color scale selected can have a significant effect on the final appearance of the image and on the clinical interpretation of myocardial perfusion. Aim – Evaluate the influence of the color scale in the qualitative analysis of MPI and study which one should be preferably used for visual interpretation of myocardial perfusion. Methods – Thirty-five MPI studies were visually interpreted by 16 nuclear medicine technologist students in the following color scales: Cool, Gray, Gray Invert, Thermal and Warm. Visual analysis of Cool’s color scale relied on a semi-quantitative scoring system. The remaining color scales were evaluated by comparison with Cool. Results/Discussion – For Cool’s color scale, inter-operator variability has shown statistically significant differences among all the participants (p<0.05), which can be assigned to the subjectivity of the visual evaluation. The results obtained for Gray and Gray Invert colors scales were the closest for the myocardial perfusion observed with Cool, being alternative color scales suited for this purpose. Regarding Thermal and Warm color scales the results were divergent, showing that they are not the optimal choice for myocardial perfusion interpretation. Conclusion – The color scale selected can influence the qualitative assessment of MPI.